FROM SECURITY TO SUSTAINABILITY: HUMAN CAPITAL DEVELOPMENT AND THE ECONOMIC FUTURE OF MALAYSIA'S DEFENCE INDUSTRY - Asmanur, Othman; Saudi, Nur Surayya Mohd; Baker, Rogis; Saudi, Mohd Haizam Mohd (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study investigates the role of Human Capital Development (HCD) in advancing Malaysia’s defence industry and its contribution to economic growth. Using time series data from 1991 to 2023, the analysis found that employment, education expenditure, and exports significantly Granger-cause GDP, underscoring the importance of skilled labour and strategic investments in education. Conversely, military expenditure and arms imports show no short-run causal impact, indicating the current defence sector's limited economic integration and technological depth. The findings reveal a critical gap between national HCD efforts and defence sector needs, hindering innovation and self-reliance. To bridge this gap, the study recommends strengthening defence-focused training, increasing investment in dual-use R&D, enhancing defence export competitiveness, and reallocating spending toward capability development. A coordinated, defence aligned with HCD strategy is essential to position the sector as both a security asset and a driver of inclusive, long-term economic growth.